Avulsion fracture of tibial insertion of PCL - operative management and outcome - Ali, M; Agrawal, P; Katakdhond, N; Arshadullah, M (Pulse, 2010)
There are controversies about the management of the PCL injuries among the Orthopaedic surgeons. We present our result of 14 cases that underwent surgical management for the avulsion fracture of the tibial insertion of the PCL. Open reduction and internal fixation of the avulsion fracture of the tibial insertion of the PCL were done and results were analyzed. The study group consisted of 13 males and 1 female; the mean age was 27 years. The avulsion fractures of more than 3 weeks old were excluded. The result showed that there were no instability in any of the patients and each patient obtained pain free, full range of movement for the affected knee within a mean follow-up period of 11 months. Therefore it is recommended to take up surgical management for avulsed PCL if presented within 3 weeks of injury. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6957 Pulse Vol.4 January 2010 p.14-15